La Curia Romana nel suo continuo processo di sviluppo: Annotazioni storico-giuridiche alla luce della riforma operata con la Costituzione Apostolica Praedicate Evangelium - Nacci, Matteo (Apollinaris, 2022)
l. Introductory note. 2. The ancient age. 3. The modem age. 4. The twentieth century. 4.1. The reform of the Roman Curia by Pius X. 4.2. The reform of the Roman Curia by Paul VI. 4.3. The reform of the Roman Curia by John Paul II 5. The contemporary age. 6. Final thought.